‘My Students Still Can’t Speak in English’: Teachers’ Beliefs and Practice in ESL Classroom / Aileen Farida Mohd. Adam ... [et al.] - Mohd. Adam, Aileen Farida; Hassan, Fauziah; Spawa, Clarvie M. Charles; Sulaiman, Mohd Suhaimi (2012)
The Integrated Syllabus for Secondary Schools (KBSM) was implemented in Malaysia in 1988. Previous studies have shown that Communicative Language Teaching (CLT) is rarely followed in the classroom although teachers claim to teach communicatively. This paper investigated teachers’ beliefs and practices in developing students’ speaking skills under the Integrated Syllabus for Secondary Schools in Malaysia. Factors which may affect teachers from using CLT in their teaching were also identified. 40 teachers participated in the semi-structured interview in order to investigate their attitudes toward CLT. Following that, two self-acclaimed communicative teachers were selected from the interview sessions for observation to verify their practices in the classroom. It was found out that both teachers acknowledge the significance of speaking in learning the English language. However, due to the national examinations, they tend not to emphasize their teaching on speaking as it is not an important component of the exam. This proves that attitudes are by no means a measurement of whether certain practices will follow. Other than that, a certain amount of discrepancy between teachers’ attitudes and practice is to be expected, depending on the particular situation. Situational constrains may prevent teachers from carrying out their practices according to their attitudes or beliefs.